Light Quality Affects Water Use of Sweet Basil by Changing Its Stomatal Development - Sungeun Lim; Jongyun Kim (Agronomy, 2021)
Different light qualities affect plant growth and physiological responses, including stomatal openings. However, most researchers have focused on stomatal responses to red and blue light only, and the direct measurement of evapotranspiration has not been examined. Therefore, we quantified the evapotranspiration of sweet basil under various red (R), green (G), and blue (B) combinations using light-emitting diodes (LEDs) and investigated its stomatal responses. Seedlings were subjected to five different spectral treatments for two weeks at a photosynthetic photon flux density of 200 µmol m−2 s−1. The ratios of the RGB light intensities were as follows: R 100% (R100), R:G = 75:25 (R75G25), R:B = 75:25 (R75B25), R:G:B = 60:20:20 (R60G20B20), and R:G:B = 31:42:27 (R31G42B27). During the experiment, the evapotranspiration of the plants was measured using load cells. Although there were no significant differences in growth parameters among the treatments, the photosynthetic rate and stomatal conductance were higher in plants grown under blue LEDs (R75B25, R60G20B20, and R31G42B27) than in the R100 treatment. The amount of water used was different among the treatments (663.5, 726.5, 728.7, 778.0, and 782.1 mL for the R100, R75G25, R60G20B20, R75B25, and R31G42B27 treatments, respectively). The stomatal density was correlated with the blue light intensity (p = 0.0024) and with the combined intensity of green and blue light (p = 0.0029); therefore, green light was considered to promote the stomatal development of plants together with blue light. Overall, different light qualities affected the water use of plants by regulating stomatal conductance, including changes in stomatal density.